2017
DOI: 10.1016/j.omtn.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

miR-206/133b Cluster: A Weapon against Lung Cancer?

Abstract: Lung cancer is a deadly disease that ends numerous lives around the world. MicroRNAs (miRNAs) are a group of non-coding RNAs involved in a variety of biological processes, such as cell growth, organ development, and tumorigenesis. The miR-206/133b cluster is located on the human chromosome 6p12.2, which is essential for growth and rebuilding of skeletal muscle. The miR-206/133b cluster has been verified to be dysregulated and plays a crucial role in lung cancer. miR-206 and miR-133b participate in lung tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Recent investigation on head and neck squamous cell carcinoma reported that miR‐206 inhibits cell invasion and migration via downregulating MMP‐2 . An increasing body of studies have demonstrated the role of miR‐206 as a tumor‐inhibiting factor in a variety of cancers, including TC …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigation on head and neck squamous cell carcinoma reported that miR‐206 inhibits cell invasion and migration via downregulating MMP‐2 . An increasing body of studies have demonstrated the role of miR‐206 as a tumor‐inhibiting factor in a variety of cancers, including TC …”
Section: Discussionmentioning
confidence: 99%
“…9 An increasing body of studies have demonstrated the role of miR-206 as a tumor-inhibiting factor in a variety of cancers, including TC. 6,8,16,18 RAP1B is a member of the small GTPase Ras family, functioning as a molecular switch and plays a crucial role in cell activities, including cell proliferation, migration, and invasion. Recent studies have revealed the abnormal occurrence of RAP1B in several malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these miRNAs, miR-206 was identified to have protective effects on the development of coronary artery disease and cancers. 15,16 In particular, studies revealed that miR-206 participated in the progression of glioma by functioning as a tumor inhibitor to regulate cellular biological processes, and decreased miR-206 expression was associated with poor prognosis in glioma. [17][18][19] Further, miR-206 knockdown was shown to protect human embryonic stem cells (hESCs) against propofol-induced cell apoptosis, thereby inhibiting neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several microRNAs (miRNAs) were also reported to modulate VEGF-A expression and to be downregulated in lung cancer cell lines. In particular, miR-126, miR-497, MiR-206, miR-29c, miR-135a, and miR-195 expression inversely correlated with VEGF-A production in different lung cancer cell lines or in patients' tumor samples [86][87][88][89][90][91]. Moreover, interleukin-17 (IL-17) was found to stimulate NSCLC-associated angiogenesis by augmenting the secretion of various angiogenic factors.…”
Section: Lung Cancermentioning
confidence: 99%